Cybersecurity in Morocco - Maleh, Yassine; Maleh, Youness (Cham : Springer International Publishing : Imprint: Springer, 2022)
This SpringerBrief contains eight chapters and presents an overview of the evolution of the Moroccan Cybersecurity Strategy. It also draws attention to the development of cybersecurity in Morocco and to ensure national security in the context of the current and developing information confrontation in the international community. However, it cannot promise to provide an in-depth examination. The issue of cybersecurity is simply too wide-ranging for our purposes. This acknowledgment is meant to encourage more detailed research into the broader topics covered in this brief to better inform current approaches to national cybersecurity performance evaluation. This SpringerBrief targets researchers interested in exploring and understanding Morocco and its efforts in implementing its national cybersecurity strategy. This brief is also a relevant reference for diplomats, executives, CISOs, cybersecurity professionals and engineers working in this related field. .
Introduction -- Understanding cybersecurity standards -- The African View on Cybersecurity -- The Moroccan View on Cybersecurity -- Morocco National Cybersecurity strategy -- National Cyber resilience Strategy in a post-COVID-19 world -- Cyber Sovereignty in Morocco -- Conclusion.
Keywords: Data protection; Computer crimes; Data and Information Security; Cybercrime; Security Services; Computer Crime